2009
DOI: 10.1186/1471-2458-9-116
|View full text |Cite
|
Sign up to set email alerts
|

A translational framework for public health research

Abstract: BackgroundThe paradigm of translational medicine that underpins frameworks such as the Cooksey report on the funding of health research does not adequately reflect the complex reality of the public health environment. We therefore outline a translational framework for public health research.DiscussionOur framework redefines the objective of translation from that of institutionalising effective interventions to that of improving population health by influencing both individual and collective determinants of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 49 publications
1
119
0
11
Order By: Relevance
“…Additionally, for any public health policy to be implemented, some level of public support is typically necessary. Although empirically supported policies are desirable, unequivocal evidence of effectiveness has been recognised as an important, but not mandatory requirement in creating public health policies (Ogilvie, Craig, Griffin, Macintyre, & Wareham, 2009). The presence of an evidence-based gambling policy, although important, is insufficient to minimise harms; policy needs to be implemented, assessed and refined (Anderson, Chisholm, & Fuhr, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, for any public health policy to be implemented, some level of public support is typically necessary. Although empirically supported policies are desirable, unequivocal evidence of effectiveness has been recognised as an important, but not mandatory requirement in creating public health policies (Ogilvie, Craig, Griffin, Macintyre, & Wareham, 2009). The presence of an evidence-based gambling policy, although important, is insufficient to minimise harms; policy needs to be implemented, assessed and refined (Anderson, Chisholm, & Fuhr, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Tal como señalan Ogilvie et al 1 , no está en disputa la idea de que la investigación básica y aplicada necesita ser transferida a otros escenarios relevantes. No obstante, existen dos preguntas críticas: ¿Qué investigación en salud requiere ser transferida?…”
Section: Investigación Traslacional En Salud: Un Camino Para La Invesunclassified
“…Critical articles have been written on the use of RCTs in development (Barrett and Carter, 2010;Cartwright, 2007;Davies et al, 2014;Eble et al, 2013;Ogilvie et al, 2009;Shaffer, 2011;Toroyan et al, 2000;Worrall, 2007). Most of these critiques focus on the lack of generalizability of RCT results (Cartwright, 2011), but others reflect on flaws with respect to their internal validity and the difficulties of replicating clinical-type experiments in a broader social context (Deaton, 2010;Shaffer, 2011).…”
Section: Randomized Trials Of Microfinancementioning
confidence: 99%
“…The sudden infant death syndrome (SIDS) campaign 'Back to Sleep', from the public health literature, illustrates the insights that can be achieved from the implementation of other research methods. The success of this campaign was determined through observational evidence that highlighted behavioural factors (position of baby) and poverty as risk factors for SIDS and could have been established two decades earlier if non-trial evidence had been synthesized in the same way that RCT evidence is (Ogilvie et al, 2009). Furthermore, incorporating qualitative methods into an evaluation, in addition to forming part of the required preparatory work of an evaluation (whether in terms of design and/or determining the adequacy or plausibility of the study); can better inform the identified pathways to effect so providing richer insights for policy makers.…”
Section: Learning From Public Health: Moving Beyond Rctsmentioning
confidence: 99%
See 1 more Smart Citation